Food Insecurity During COVID-19: A Neglected Priority? - Haron, Muhammad Zulfahmi; Abdul Jalil, Rohana (IIUM Medical Journal Malaysia, 2023)
The COVID-19 pandemic is a public health and global problem threatening the food security and nutrition of millions of people. While considerable public health resources have focused on combating the COVID-19 pandemic, food and nutrition have received less attention. By 2030, Sustainable Development Goal 2 aims to eradicate hunger and ensure that all people, especially the poor and vulnerable, have year-round access to safe, nutritious, and enough food. Regrettably, the world is falling short of its 2030 target of attaining Zero Hunger, mainly due to this pandemic. We reviewed the prevalence of food insecurity during COVID-19 ranging from 23% to 80% and its consequences including the measures presented in the previous studies to address the issue. Food insecurity has many negative consequences during COVID-19, including disruption of food chains, increased food prices, malnutrition and health consequences, growing social inequities, and bad economic outcomes. We highlighted the need for two main strategies: nutritionsensitive social protection, and food system reform and innovation to address this problem further to build a more robust and resilient food system for the sake of future generations.